Biophysical characterization of peptide–membrane interactions. Issue 1 (1st January 2018) - Lee, Ming-Tao
Abstract: Membrane active peptides directly target membranes rather than receptor proteins and perform their biological functions via cooperative action. To understand the mechanism of peptide–membrane interactions, biophysical characterization of the whole interaction process is essential. The characteristics determined by biophysical methods are briefly summarized and the limitations of these techniques discussed. Circular dichroism (CD), isothermal titration calorimetry (ITC), and fluorescence have been used to determine the binding isotherms of peptide binding to membranes in solution. Lamellar X-ray diffraction (LXD) and small single X-ray scattering (SAXS) have been used to probe peptide-induced thinning of membranes on a substrate and in solution, respectively. The aspiration method has been applied to monitor the area expansion induced by peptide binding to single giant unilamellar vesicles (GUVs). Oriented circular dichroism (OCD) has been used to detect orientation changes of peptides in membranes. The inner water columns of peptide-induced pores in membranes were detected by neutron scattering (NS), and pore structures were reconstructed using anomalous X-ray diffraction. Finally, the time evolution of pore formation induced by peptides binding to single GUVs was monitored by the aspiration method. Abstract :